2010
DOI: 10.1111/j.1365-2923.2010.03631.x
|View full text |Cite
|
Sign up to set email alerts
|

Residents’ reasons for specialty choice: influence of gender, time, patient and career

Abstract: OBJECTIVE This study examined reasons for specialty choice among Swiss residents (post graduate doctors training in specialties). METHODS In 2006, a questionnaire was sent to 8626 Swiss residents registered in postgraduate medical training programmes to obtain specialist qualifications. The response rate was 65% (n = 5631). As residents are allowed to decide on the specialty they want to acquire later in the training process, only residents who had already chosen a specific specialty were included (n = 5038). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 16 publications
2
62
1
4
Order By: Relevance
“…This was found to be consistent with previous studies published on this topic 14 . A study done in United Kingdom on 15,759 doctors showed that about a quarter of doctors were working in a specialty that was different from the one chosen in their third year after graduation 13 .Another study found out that a disproportionately higher percentage of women considered but rejected a career in surgery.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This was found to be consistent with previous studies published on this topic 14 . A study done in United Kingdom on 15,759 doctors showed that about a quarter of doctors were working in a specialty that was different from the one chosen in their third year after graduation 13 .Another study found out that a disproportionately higher percentage of women considered but rejected a career in surgery.…”
Section: Discussionsupporting
confidence: 94%
“…The highest match rate found in this study was for specialty choice they made five yearsafter graduation. The greatest increase in match rate occurred between one year after graduation and three years after graduation indicating that this period was the key period in which the final choice of specialty is made 16 .Training duration and gender differences in reason for choosing a specialty may become more pronounced with passage of time and can lead to change in preferred specialty 14 . Night duties were the most common cause amongst resident to leave their current specialty training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literature has explored many possible factors that affect specialty choice, including personality and values [18], medical school experiences and financial aid [19], and gender [20]. Research has also shown that residents’ reasons for choosing a specific specialty varies by specialty [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…2 Studies of doctors' choice of specialty tend to focus on what they choose, and why, rather than what they reject and why. 3 In recent national surveys of doctors' career choices in the UK, we have asked both about positive specialty choices and about any specialty that the doctors have seriously considered and then not pursued. We report here on the findings from surveys of graduates of 2002, 2005 and 2008 undertaken towards the end of the first postqualification year.…”
Section: Introductionmentioning
confidence: 99%